Analysis of quota policies in state public universities in the state of Paraná/Brazil, according to the Policy Cycle - Andreliza Cristina de Souza; José Carlos Rothen (Arizona State University, 2021)
The study aims to analyze the quota policies for black students from public school of five state public universities of the state of Parana, in Brazil, concerning its similarities and differences, potentials and limits, strategies and procedures used for implantation and implementation of set-aside policies. Institutional documents as well as semi-structured interviews with institutional actors were used as data source. The Cycle of Policies was used for the analysis through which contexts of influence, text production and practices of quotas were exploited (Ball et al., 2016; Bowe et al., 1992). Finishing up the analysis, it was noticed that each university adopted different models of quotas according to its possibilities and limitations. The actors involved in the quotas also went through difficulties during the process, from the text production to its implementation. According to the reports, it was possible to verify that the text production generated limitations to the access of black male and female students from public school, which could have been greater since the first years of the adoption of quotas. The lack of evaluation and monitoring was also highlighted in the analysis, which is a weakness of quotas in higher education institutions.